2001
DOI: 10.1080/028275801300004398
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Plant Community Structure Across a Primary Succession Gradient

Abstract: Microbial and plant community structure across a primary succession gradient.The formation of the organic layer within Scandinavian forest soil started about 10 000 yr ago, following the retreat of the continental ice sheet. Since then the land has been slowly rising in northern Europe and uplift still occurs on the coast of the Bothnian Bay at a rate of about 0.6 ± 0.9 m per 100 yr. Four, 300 m long, successional gradients were studied from the shoreline to a Scots pine (Pinus syl×estris) stand with a fully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…The lowest number of isolates per root system was obtained from the early successional dune ridge (0.5 per root system) and highest from the late successional site (1.5 per root system). Although the goal of this study was not to monitor the absolute number of strains between different successional stages and the number of samples varied between sites, our result is in line with the reports on increased fungal abundance along with increasing soil successional age (Pennanen et al 2001). The sequencing of the isolates revealed that most of the fungal strains were conspecific with the dark septate endophyte Phialocephala fortinii (27 strains out of 38).…”
Section: Culturable Fungal Endophytessupporting
confidence: 91%
See 3 more Smart Citations
“…The lowest number of isolates per root system was obtained from the early successional dune ridge (0.5 per root system) and highest from the late successional site (1.5 per root system). Although the goal of this study was not to monitor the absolute number of strains between different successional stages and the number of samples varied between sites, our result is in line with the reports on increased fungal abundance along with increasing soil successional age (Pennanen et al 2001). The sequencing of the isolates revealed that most of the fungal strains were conspecific with the dark septate endophyte Phialocephala fortinii (27 strains out of 38).…”
Section: Culturable Fungal Endophytessupporting
confidence: 91%
“…The mineral soil in the seashore is sand with low total nitrogen content. Soil organic matter increases and soil pH decreases along the succession gradient towards late succession (Pennanen et al 2001). The plant material was collected in early growing season, (June 5th, 2007) from five sites representing four kinds of habitats: Site 1: A sandy seashore dune ridge area with only occasional patches of Empetrum nigrum L. (subspecies hermaphroditum, referred to as Empetrum nigrum hereafter) and the grasses Deschampsia flexuosa L. and Agrostis spp.…”
Section: Collection Of Plant Materialsmentioning
confidence: 98%
See 2 more Smart Citations
“…Along with this variation in microbial community composition, microbial function, as measured through nutrient Society"pp.133 -145 (2017) turnover, changes may also occur on a seasonal basis (DeForest et al, 2009). Previous studies examining relationship between vegetation patchiness and microbial communities were conducted in a forest ecosystem (Pennanen et al, 2001) or volcanic desert ecosystem (Yoshitake et al, 2013). However, studies on examining the bacterial communities and activity associated with patchiness of halophytic vegetation in an extreme saline-alkali wet land are rare.…”
Section: Introductionmentioning
confidence: 99%